2022
DOI: 10.3390/nano12050861
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Dynamics Simulation Study of the Self-Assembly of Phenylalanine Peptide Nanotubes

Abstract: In this paper, we propose and use a new approach for a relatively simple technique for conducting MD simulation (MDS) of various molecular nanostructures, determining the trajectory of the MD run and forming the final structure using external force actions. A molecular dynamics manipulator (MD manipulator) is a controlled MDS type. As an example, the applicability of the developed algorithm for assembling peptide nanotubes (PNT) from linear phenylalanine (F or Phe) chains of different chirality is presented. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(17 citation statements)
references
References 75 publications
1
14
0
2
Order By: Relevance
“…The major finding in this study is that we demonstrate the helical assembly behavior of one short‐acting oral antidiabetic compound NG into left‐handed nanofibers, which is probably due to the existence of chiral phenylalanine residue on the backbone of the molecular structure. However, very different to the self‐assembly of pure phenylalanine‐based peptides as previously reported, [ 50 ] the chiral assembly of NG occurs with aid of divalent cations under alkaline condition. At molecular level, MD simulations clearly revealed that ionic interaction between Ca 2+ and deprotonated carboxylate anion of NG plays a vital role in maintaining the chiral assembly configuration accompanied by the interactions between benzene rings of NG.…”
Section: Discussionmentioning
confidence: 68%
“…The major finding in this study is that we demonstrate the helical assembly behavior of one short‐acting oral antidiabetic compound NG into left‐handed nanofibers, which is probably due to the existence of chiral phenylalanine residue on the backbone of the molecular structure. However, very different to the self‐assembly of pure phenylalanine‐based peptides as previously reported, [ 50 ] the chiral assembly of NG occurs with aid of divalent cations under alkaline condition. At molecular level, MD simulations clearly revealed that ionic interaction between Ca 2+ and deprotonated carboxylate anion of NG plays a vital role in maintaining the chiral assembly configuration accompanied by the interactions between benzene rings of NG.…”
Section: Discussionmentioning
confidence: 68%
“…Самоорганизация сложных биомолекулярных структур является одним из важнейших явлений в природе. Примером самоорганизующихся макромолекулярных систем являются пептидные нанотрубки (ПНТ) на основе аминокислоты фенилаланина (F) и ее дипептида -дифенилаланина (FF) [26][27][28][29][30][31][32]. Благодаря широкому спектру свойств эти структуры являются перспективными для применений в нанотехнологиях, наноэлектронике и биомедицине.…”
Section: исследования пептидных нанотрубок на основе аминокислотunclassified
“…Для моделирования самосборки ПНТ были применены также методы МД и получены хорошие статистически значимые результаты по такой МД самосборке, соответствующие экспериментальным данным (рис. 7) [30]. Установлена была сильная поляризация ПНТ, обусловленная дипольными моментами дипептидов [26][27][28]31]; исследовано влияние молекул воды во внутренней полости ПНТ, их роли в свойствах ПНТ [26][27][28][29] и определено их оптимальное количество.…”
Section: исследования пептидных нанотрубок на основе аминокислотunclassified
“…Previously, we already considered the application of computer simulation methods to the study of peptide nanotubes of different chirality [ 7 , 12 , 13 , 14 , 15 , 28 , 29 ]. The formation of a helical structure of a peptide nanotube (PNT) based on phenylalanine (F/Phe) was also considered using MDS methods [ 30 , 31 ]. It is known that, based on these amino acids, nanotubes of the F PNT type are also formed [ 32 , 33 ], as well as dipeptides and diphenylalanine (FF/(Phe) 2 ), which, in turn, self-assemble into peptide diphenylalanine nanotubes [ 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 19 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 ].…”
Section: Introductionmentioning
confidence: 99%